The Level of Member Satisfaction and Its Influence on Member Participation In The Rimbun Jaya 3 Producer Cooperative In Way Harong Village, Waylima District, Pesawaran Regency - Bagas Luansah; Dyah Aring Hepiana Lestari; Ani Suryani (Jurnal Penelitian Pertanian Terapan, 2025)
Cooperatives play a vital role in improving the welfare of their members by providing various economic benefits and promoting collective participation. Member satisfaction creates a positive attitude towards the cooperative, more satisfied members will support the cooperative by participating in cooperative activities. This study aims to analyze the satisfaction felt by members towards cooperative services and as cooperative members, the level of member participation, and the factors that influence it. This study was conducted using a survey method at the Rimbun Jaya 3 Producer Cooperative, Way Harong Village, Way Lima District, Pesawaran Regency. Data collection was carried out from December 2023 to January 2024. The sample size of cooperative member was 55 people selected using the simple random sampling method. Data were analyzed using quantitative descriptive, the Customer Satisfaction Index (CSI), and Seemingly Unrelated Regressions (SUR) methods. The results showed that members were very satisfied with the cooperative's services and satisfied as cooperative members. Member participation in attending the Annual Members Meeting (RAT) was at high level, member participation in paying mandatory savings was at medium level, and member participation in utilizing business units was at low level. Factors that influence member participation in attending the RAT include age, membership duration, education level, household income, satisfaction with cooperative services, satisfaction as a member, and distance from the home to the cooperative. Household income, non-formal education, and distance from the home to the cooperative affect member participation in paying mandatory savings. Age, household income, satisfaction with services, non-formal education, and distance from the home to the cooperative affect member participation in utilizing cooperative business units.